"Decimal system among the ancient Peruvians": an example of the essay genre little studied in Ricardo Palma - Ward, Thomas (2023)
This article will examine “Sistema decimal entre los antiguos peruanos” by Ricardo Palma. Palma’s essay argues that the Inkas used the decimal system by departing from a philological analysis of Ollantay and the Royal Commentaries of Inca Garcilaso de la Vega. It will consider why this piece is an essay and not a tradición by comparing its constituent elements with the characteristics of the essay as Gómez Martínez theorizes them, including discursivity, lack of a rigid structure, inciting reflection, digression, and vagueness in quoting practices. If Palma does a philological study of Ollantay and the Royal Commentaries, the present article will complete a philological study of Palma’s “Sistema decimal”. Keywords: Ricardo Palma, “Sistema decimal”, essay, discursivity, Inca Garcilaso de la Vega, Ollantay, Peruvian literature.